2014
DOI: 10.1186/1756-3305-7-397
|View full text |Cite
|
Sign up to set email alerts
|

Integrated mapping of lymphatic filariasis and podoconiosis: lessons learnt from Ethiopia

Abstract: BackgroundThe World Health Organization (WHO), international donors and partners have emphasized the importance of integrated control of neglected tropical diseases (NTDs). Integrated mapping of NTDs is a first step for integrated planning of programmes, proper resource allocation and monitoring progress of control. Integrated mapping has several advantages over disease specific mapping by reducing costs and enabling co-endemic areas to be more precisely identified. We designed and conducted integrated mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 30 publications
(40 reference statements)
2
70
0
Order By: Relevance
“…47 Further still, studies have shown that the negative predictive value of using a mere clinical assessment in making a podoconiosis diagnosis exceeds 90%, compared with the WHO gold standard. 48 In conclusion, our investigation revealed nonfilarial elephantiasis consistent with podoconiosis in an area not previously known to be endemic with this disease. Prolonged foot exposure to irritant volcanic soils (as a result of not wearing protective foot wear while at work and home and delayed foot washing to get rid of irritant soils) was strongly associated with the disease.…”
Section: Discussionsupporting
confidence: 54%
“…47 Further still, studies have shown that the negative predictive value of using a mere clinical assessment in making a podoconiosis diagnosis exceeds 90%, compared with the WHO gold standard. 48 In conclusion, our investigation revealed nonfilarial elephantiasis consistent with podoconiosis in an area not previously known to be endemic with this disease. Prolonged foot exposure to irritant volcanic soils (as a result of not wearing protective foot wear while at work and home and delayed foot washing to get rid of irritant soils) was strongly associated with the disease.…”
Section: Discussionsupporting
confidence: 54%
“…Mobile phone technology has the potential to enhance community engagement through encouraging and simplifying the exchange of information between community members and health programmes. Examples of mobile health (or mHealth) can be found in a variety of applications including disease mapping/surveillance [ 10 , 11 ], health education, monitoring treatment compliance [ 12 ], early warning systems [ 13 ] and medical supply chain management [ 14 ]. In particular, the combination of community-led health systems and mHealth tools has proven to be successful in improving HIV-infected patient care [ 15 ], real-time reporting of malaria cases [ 16 ], antimalarial supply monitoring [ 17 ] and supporting health worker-patient interactions [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this study, 11 lymphoedematous patients with podoconiosis and nodules on the foot were recruited. Podoconiosis as the cause of the lymphoedema was diagnosed in the usual way: typical clinical features and the known absence of lymphatic filariasis in the region . There are no specific tests to confirm the diagnosis of podoconiosis.…”
Section: Summary Of Demographics and Resultsmentioning
confidence: 99%